International yearbook of educational and training technology (New york : Kogan Page, 1980)
Lists more than 1500 institutions of higher education and other organizations involved in the field of educational and training technology. Each entry contains information on areas of interest, current and future projects and publications. It is indexed by key word and institution
Keywords: Educational technology; Programmed instruction; Programmed instruction